calcule o valor numérico da expressão 5k-1/2 para os valores de k=0, K=-3, k=-4, k=3 e k=-1
Soluções para a tarefa
Respondido por
3
Para k=0 ( so substituir) V(k)
![V(k)= 5k - \frac{1}{2} V(k)= 5k - \frac{1}{2}](https://tex.z-dn.net/?f=V%28k%29%3D+5k+-+%5Cfrac%7B1%7D%7B2%7D+)
![V(0)= 5.0 - \frac{1}{2} V(0)= 5.0 - \frac{1}{2}](https://tex.z-dn.net/?f=V%280%29%3D+5.0+-+%5Cfrac%7B1%7D%7B2%7D+)
![V(0)= 0 - \frac{1}{2} V(0)= 0 - \frac{1}{2}](https://tex.z-dn.net/?f=V%280%29%3D+0+-+%5Cfrac%7B1%7D%7B2%7D+)
![V(0)= - \frac{1}{2} V(0)= - \frac{1}{2}](https://tex.z-dn.net/?f=V%280%29%3D++-+%5Cfrac%7B1%7D%7B2%7D+)
Para k= -3
![V(-3)= 5.(-3) - \frac{1}{2} V(-3)= 5.(-3) - \frac{1}{2}](https://tex.z-dn.net/?f=V%28-3%29%3D+5.%28-3%29+-++%5Cfrac%7B1%7D%7B2%7D+)
![V(-3)= -15 - \frac{1}{2} V(-3)= -15 - \frac{1}{2}](https://tex.z-dn.net/?f=V%28-3%29%3D+-15+-++%5Cfrac%7B1%7D%7B2%7D+)
![V(-3)= -15. \frac{2}{2} - \frac{1}{2} V(-3)= -15. \frac{2}{2} - \frac{1}{2}](https://tex.z-dn.net/?f=V%28-3%29%3D+-15.+%5Cfrac%7B2%7D%7B2%7D++-++%5Cfrac%7B1%7D%7B2%7D+)
![V(-3)= - \frac{30}{2} - \frac{1}{2} V(-3)= - \frac{30}{2} - \frac{1}{2}](https://tex.z-dn.net/?f=V%28-3%29%3D+-+%5Cfrac%7B30%7D%7B2%7D++-++%5Cfrac%7B1%7D%7B2%7D+)
![V(-3)= - \frac{31}{2} V(-3)= - \frac{31}{2}](https://tex.z-dn.net/?f=V%28-3%29%3D+-+%5Cfrac%7B31%7D%7B2%7D+++)
Para k = -4
![V(-4) = 5. (-4) - \frac{1}{2} V(-4) = 5. (-4) - \frac{1}{2}](https://tex.z-dn.net/?f=V%28-4%29+%3D+5.+%28-4%29+-+%5Cfrac%7B1%7D%7B2%7D+)
![V(-4) = -\frac{21}{2} V(-4) = -\frac{21}{2}](https://tex.z-dn.net/?f=V%28-4%29+%3D+-%5Cfrac%7B21%7D%7B2%7D+)
Para k = 3
![V(3)= 5.3 - \frac{1}{2} V(3)= 5.3 - \frac{1}{2}](https://tex.z-dn.net/?f=V%283%29%3D+5.3+-+%5Cfrac%7B1%7D%7B2%7D+)
![V(3)= \frac{29}{2} V(3)= \frac{29}{2}](https://tex.z-dn.net/?f=V%283%29%3D+%5Cfrac%7B29%7D%7B2%7D+)
Para k=1
![V(1) = 5.1- \frac{1}{2} V(1) = 5.1- \frac{1}{2}](https://tex.z-dn.net/?f=V%281%29+%3D+5.1-+%5Cfrac%7B1%7D%7B2%7D+)
![V(1) =\frac{9}{2} V(1) =\frac{9}{2}](https://tex.z-dn.net/?f=V%281%29+%3D%5Cfrac%7B9%7D%7B2%7D+)
Para k= -3
Para k = -4
Para k = 3
Para k=1
Respondido por
3
Resposta:
Explicação passo-a-passo:
Perguntas interessantes
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Matemática,
11 meses atrás
Português,
1 ano atrás
Geografia,
1 ano atrás